2015
DOI: 10.1007/s00253-014-6307-1
|View full text |Cite
|
Sign up to set email alerts
|

Sigma factor WhiGch positively regulates natamycin production in Streptomyces chattanoogensis L10

Abstract: The roles of many sigma factors are unclear in regulatory mechanism of secondary metabolism in Streptomyces. Here, we report the regulation network of a group 3 sigma factor, WhiGch, from a natamycin industrial strain Streptomyces chattanoogensis L10. WhiGch regulates the growth and morphological differentiation of S. chattanoogensis L10. The whiG ch deletion mutant decreased natamycin production by about 30 % and delayed natamycin production more than 24 h by delaying the growth. Overexpression of the whiG ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…It is generally uncommon for global/pleiotropic regulators to directly control structural genes involved in antibiotic biosynthesis; however, similar phenomena have been observed in other Streptomyces species. For instance, WhiG from S. chattanoogensis L10, an industrial natamycin producer, controls natamycin production as well as spore development44. It directly activates natamycin production by binding to the promoters of biosynthetic genes scnC and scnD .…”
Section: Discussionmentioning
confidence: 99%
“…It is generally uncommon for global/pleiotropic regulators to directly control structural genes involved in antibiotic biosynthesis; however, similar phenomena have been observed in other Streptomyces species. For instance, WhiG from S. chattanoogensis L10, an industrial natamycin producer, controls natamycin production as well as spore development44. It directly activates natamycin production by binding to the promoters of biosynthetic genes scnC and scnD .…”
Section: Discussionmentioning
confidence: 99%
“…In S. coelicolor , σ B (Cho et al, 2001; Lee et al, 2004b) and σ K (Mao et al, 2009) are involved in regulation of ACT and RED biosynthesis, although the regulatory mechanisms are unclear. In Streptomyces chattanoogensis L10, alternative σ factor WhiG ch promotes natamycin biosynthesis by directly activating two structural genes, scnC and scnD (Liu S. P. et al, 2015). In the present study, we characterized alternative σ factor σ 8 in S. avermitilis , and demonstrated that it indirectly represses avermectin production through its effects on expression of CSR gene aveR and structural gene aveA1 .…”
Section: Discussionmentioning
confidence: 99%
“…Other inter-species differences were previously noted between S. coelicolor and S. griseus 78 . A different kind of surprise concerning the WhiG sigma was the discovery in Streptomyces chattanoogensis that it can bind to target promoters in the absence of RNA polymerase core enzyme, including some in the gene cluster for natamycin production: binding was either to typical WhiG-binding sites or to CGTCA repeat elements, and was needed for gene activation 79 .…”
Section: New Perspectives In Growth and Development Of Streptomycesmentioning
confidence: 99%